Bear snores on eaudiobook - Wilson, Karma (Bear., 2016)
Acclaimed author Karma Wilson tells a festive story about friendship and helping others when they are sad in this Children's Book-of-the-Month Club Featured Selection. Bear is snuggled in his cave for the winter. He sleeps all day and all night. The cold wind can't even wake him up. He just snores on. Then, one day, something unexpected happens, and he is woken up. John McDonough's playful narration helps listeners become involved in these woodland creatures' activities.